Unsaturated polyurethane films grafted with enantiomeric polylysine promotes macrophage polarization to a M2 phenotype through PI3K/Akt1/mTOR axis. (July 2020) - Duan, Yiyuan; Zheng, Honghao; Li, Zehua; Yao, Yuejun; Ding, Jie; Wang, Xuemei; Nakkala, Jayachandra Reddy; Zhang, Deteng; Wang, Zhaoyi; Zuo, Xingang; Zheng, Xiaowen; Ling, Jun; et al.
Abstract: The immune system responds immediately to tissue trauma and to biomaterial implants under the participation of M1/M2 macrophages polarization. The surface properties of biomaterials can significantly influence the tissue repair progress through modulating the macrophage functions. In this study, the surface of poly(propylene fumarate) polyurethane films (PPFU) is grafted with a same density of enantiomeric poly-l -lysine (PPFU-g-PLL) and poly-d -lysine (PPFU-g-PDL), leading to a similar level of enhanced surface wettability for the PPFU-g-PLL and PPFU-g-PDL. The polylysine-grafted PPFU can restrict the M1 polarization, whereas promote M2 polarization of macrophages in vitro, judging from the secretion of cytokines and expression of key M1 and M2 related genes. Comparatively, the PPFU-g-PDL has a stronger effect in inducing M2 polarization in vivo, resulting in a thinner fibrous capsule surrounding the implant biomaterials. The CD44 and integrins of macrophages participate in the polarization process probably by activating focal adhesion kinase (FAK) and Rho-associated protein kinase (ROCK), and downstream PI3K/Akt1/mTOR signal axis to up regulate M2 related gene expression. This study confirms for the first time that polylysine coating is an effective method to regulate the immune response of biomaterials, and the polylysine-modified thermoplastic PPFU with the advantage to promote M2 polarization may be applied widely in regenerative medicine.